Bioethical considerations on chronic diseases in childhood - Alina Esther González Hermida; Yanet de la C. Fragoso Cordero; Gisela Zerquera Trujillo; Hussimyn Marchena Morera; Carmen Guerra Cabrera (Medisur)
-